(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless Ad-hoc Sensor Networks (WSN) is a recent advanced technology of computer networks and electronics. The WSN are increasingly becoming more practicable solution to many challenging applications. The wireless ad hoc sensor networks depend upon the sensed data, which may depend upon the application and various operations require different algorithms for their routing from one point to another. This paper presents a comparative analysis of routing protocols in ad-hoc sensor networks. This paper will study the working of some well-known routing protocols like DSDV, ADOV, DSR AND IMEP. The most important characteristic is the dynamic topology, which is a consequence of node mobility. Nodes can change their positions quite frequently, which mean that we need a routing protocol that quickly adapts to topology changes. The nodes in an ad-hoc network can consist of laptops and personal digital assistants and are often very limited in resources such as CPU capacity, storage capacity, battery power and bandwidth. This means that the routing protocol should try to minimize control traffic, such as periodic update messages. Instead the routing protocol should be reactive, which means it only calculates routes upon receiving a specific request.